The Effectiveness of Guided Inquiry Learning Models for Students' Scientific Performances and Critical Skills - Supriyatno, Triyo; Lestari, Dirga Ayu; Utami, Ulfa (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2020)
This study aims to analyze learning activities using guided inquiry learning models in improving scientific attitudes and students 'critical thinking skills and the effectiveness of guided inquiry learning models in improving scientific attitudes and students' critical thinking skills in science learning. This research was a quasi-experimental research with purposive sampling technique. Subjects in this study were 51 students of class V MIN 1 Serang. Data collection used documentation, questionnaires, observations and tests. Data were collected from the pretest and posttest of the students' scientific attitude and critical thinking as well as documentation and observation of guided inquiry learning activities in the control class and the experimental class. The type of data analysis used t-Test and effect size cohen’s test with the help of the statistical package for the social sciences (SPSS) program version 23.0. The results showed that the guided inquiry model learning activities were better than conventional models namely. So, there is the effectiveness of guided inquiry learning models in improving scientific attitudes and critical thinking skills of students on science learning in class.